2008
DOI: 10.2334/josnusd.50.123
|View full text |Cite
|
Sign up to set email alerts
|

Oral clefts: a retrospective study of prevalence and predisposal factors in the State of Mexico

Abstract: The purpose of this study was to up-date the records concerning oral clefts (OCs) encountered at the Child Hospital of the Maternal Infantile Institute of the State of México, and to examine the association of predisposing factors. A retrospective study of the medical records of patients generated over a 5-year period was carried out. A total of 835 files were reviewed, representing 504 boys and 331 girls. The studied variables were the type of oral clefts and predisposing factors. Kendal correlations at P < o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
21
2
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 30 publications
7
21
2
12
Order By: Relevance
“…This supports other studies that reported an association between agricultural work and/or exposure to pesticides experienced by the father, or the mother, or both; and different adverse reproductive effects such as congenital malformations in general [23][24][25], cleft lip and palate [26][27], musculoskeletal defects [28], limb reduction defects [29][30], and central nervous system defects [31][32][33]. Environmental or occupational exposure to pesticides may cause alterations in the male gametes prior to conception, as well as embryonic damage or feto-placental complex.…”
Section: Discussionsupporting
confidence: 79%
“…This supports other studies that reported an association between agricultural work and/or exposure to pesticides experienced by the father, or the mother, or both; and different adverse reproductive effects such as congenital malformations in general [23][24][25], cleft lip and palate [26][27], musculoskeletal defects [28], limb reduction defects [29][30], and central nervous system defects [31][32][33]. Environmental or occupational exposure to pesticides may cause alterations in the male gametes prior to conception, as well as embryonic damage or feto-placental complex.…”
Section: Discussionsupporting
confidence: 79%
“…Maternal occupational exposure to toxic agents seems a priori to have a more direct effect on CL/P, and was previously shown to be associated with an increased risk of CL/P in offspring [15,16,22,25]. Experimental data support this: an increased incidence of oral clefts in offspring was noticed when pregnant mice were exposed to the herbicide 2,4,5-trichlorophenoxyacetic acid (2,4,5-T) [26].…”
Section: Discussionmentioning
confidence: 68%
“…Although the risk factors for this disease were unknown, maternal and paternal age, abortion rate, parity and mother's occupational exposure (agricultural production and exposure to pesticides) might specifi cally infl uence this trend. [26] But the increasing incidence of OFC in our area is still unexplained and further studies are required to examine the epidemiology and risk factors of this disease in China.…”
Section: Discussionmentioning
confidence: 98%